Business models in business networks – how do they emerge?. Issue 3 (16th October 2017) - La Rocca, Antonella; Snehota, Ivan
Abstract : Purpose: The expanding body of research on business models generally assumes that firms operate in a "transactional" context. Several recent studies suggest that the concept of business models in contexts where relationships matter, such as business markets, involves issues that the transactional microeconomic perspective is ill suited to capture. In the expanding literature on business models, the role of context in how business models emerge and evolve is a topic that appears under researched. The purpose of this paper is to review the findings of these studies and explore how "relational context" affects the emergence and evolution of business models. Design/methodology/approach: The authors review the literature on business models in business markets where high-involvement relationships with customers and suppliers are common, and report a case to illustrate the critical issues involved. Findings: The authors find that context where high-involvement relationships are common implies that business models are relationship specific and tend to be different across key relationships of a business; the involvement of others limits the autonomy of a single business in developing its business model; business models are continuously emergent and transient. Originality/value: This study is among the few that examine the emergence and evolution of business model in business network in a longitudinal perspective. The value of the study also lies in the implications of the relationship-centric business model for management practice and research.